A Case Associated with Comorbidities Among Cerebral Infarction, Idiopathic Thrombocytopenic Purpura, and Triple X Syndrome - Hanjun Kim; Sang Sun Hwang; Young Uh; Juwon Kim; Kap Jun Yoon; Ji Yong Lee (Turkish Journal of Hematology, 2014)
A 46-year-old female presented to the emergency room due to the chief complaint of left-sided weakness. By imaging study, she was diagnosed with cerebral infarction. Thrombolytic and antiplatelet agents were not considered due to the 'golden hour' for treatment having passed and a low platelet count. The peripheral blood smear, bone marrow biopsy, and aspirate findings were consistent with immune thrombocytopenic purpura. The chromosome analysis revealed the 47,XXX karyotype. To the best of our knowledge, this is the first case report associated with the comorbidities of cerebral infarction, idiopathic thrombocytopenic purpura, and triple X syndrome.